Edukasi dan Giat Literasi Kelautan untuk Meningkatkan Kesadaran Lingkungan di Kalangan Siswa SMA Kabupaten Mempawah - Apriansyah; Mega Sari Juane Sofiana; Arie Antasari Kushadiwijayanto; Yusuf Arief Nurrahman; Ikha Safitri; Warsidah; Nora Idiawati; Sukal Minsas; Shifa Helena; Syarif Irwan Nurdiansyah; Dwi Imam Prayitno; Tia Nuraya; Harianto; Surya Darma (Indonesian Journal Publisher, 2025)
The research aims to enhance marine literacy and raise awareness among high school students in Mempawah Regency about vital role of mangrove ecosystems in maintaining coastal environmental balance. Limited student understanding has contributed to low participation in conservation efforts. A participatory educational approach was implemented through material presentation, interactive discussion, and marine equipment demonstrations. Questionnaire results indicated that over 90% of participants reported an increased understanding, with most expressing motivation to engage in mangrove conservation activities. These findings highlight the effectiveness of participatory methods in fostering marine literacy and environmental awareness. The program’s success is expected to serve as a sustainable model for environmental education in schools and can be expanded to promote ecological consciousness at the community level.